TOPICAL APPLICATION OF ETHANOL EXTRACT OF STARFRUIT LEAVES (AVERRHOA BILIMBI LINN) INCREASES FIBROBLASTS IN GINGIVAL WOUNDS HEALING OF WHITE MALE RATS - Hartini, IGAA (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
ABSTRACT Injuries to the gingiva are often encountered because of abnormalities in the oral cavity. Gingival wound healing is more complex because it lies in an open area, often contaminated and exposed to various types of bacteria in the oral cavity. Gingiva wound healing is determined by increase of fibroblasts. Plants widely used by humans as medicine is star fruit (Averrhoa Bilimbi Linn). This study aims to determine an increase of gingival fibroblasts on wound healing of male white rats given various concentrations of starfruit leaves extract topically. The study was conducted with a pretest-posttest control group design, consisted of four groups: the control group with distilled water and the groups treated with ethanol extract of starfruit leaves with a concentration of 10%, 20% and 40%. The result based on comparison test between the groups with One Way Anova, showed that the average amount of fibroblast in four groups after receiving the treatment was significantly different (p<0.01). The result of the test showed an increase in the number of fibroblasts in groups concentration of 10% and 20%, there was a decline observed in group concentration of 40%. It was concluded that application of ethanol extract of starfruit leaves with concentration of 10% increase the highest number of fibroblasts in the rat gingival wound healing process.